If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9u + 7 = 5(u + 3) Reorder the terms: 7 + 9u = 5(u + 3) Reorder the terms: 7 + 9u = 5(3 + u) 7 + 9u = (3 * 5 + u * 5) 7 + 9u = (15 + 5u) Solving 7 + 9u = 15 + 5u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-5u' to each side of the equation. 7 + 9u + -5u = 15 + 5u + -5u Combine like terms: 9u + -5u = 4u 7 + 4u = 15 + 5u + -5u Combine like terms: 5u + -5u = 0 7 + 4u = 15 + 0 7 + 4u = 15 Add '-7' to each side of the equation. 7 + -7 + 4u = 15 + -7 Combine like terms: 7 + -7 = 0 0 + 4u = 15 + -7 4u = 15 + -7 Combine like terms: 15 + -7 = 8 4u = 8 Divide each side by '4'. u = 2 Simplifying u = 2
| 6(w+1)=2*w+34 | | 6x(6+4x)=26+x | | -8*v-2=-6(v-1) | | .125D-3(D-7)=5.125D-3 | | 21=-7*u+4(u+6) | | x^2-xy+3x^2+4xy= | | 2(v-7)+5*v=28 | | (x+1)(x-2)/x+3 | | 2(x+4)+3*x=-12 | | 7*y+23=4*y+8*y-22 | | x/5-12=4 | | -8=5x+3 | | k(2)-25=0 | | 2y+3=(y+21) | | 6*y+5=8*y+11 | | 28+19*x=-8+15*x | | 6x+8=11-4c | | -83=2*v-15*v-18 | | x+x+6x=119+6x | | 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 | | 4*x+43+2*x=7 | | (0.3+2x)(0.5+2x)=5.3018 | | -9*x-2*x-18=26 | | 108+(5x+8)=x | | -(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | x/2+x/4+x/5=x-1 | | w*5-7+w*2=-17 | | 3*3=8 |